MANAJERIAL KEPALA SEKOLAH DALAM MENCIPTAKAN SEKOLAH EFEKTIF STUDY DI SDIT AL INSANUL KAMIL TYTYAN INDAH BEKASI - Dimyati, Mochamad; Irwansyah, Saripudin; Victorynie, Irnie (Universitas Muhammadiyah Tapanuli Selatan, 2024)
In the world of education, the realization of effective schools is considered very important to achieve. In the process of realizing effective schools, the principal plays a significant role in making it happen. Thus, strategies in the process of school realization are expected to produce breakthroughs that can benefit many people. This research uses the interview method to examine the actions taken by principals in realizing effective schools. The results of this study show that the role of the principal is crucial in developing strategies to realize effective schools, which can make the learning process increasingly optimal.